2017
DOI: 10.13075/ijomeh.1896.00971
|View full text |Cite
|
Sign up to set email alerts
|

Differences in nutritional status of preschool children in the context of the maternal social characteristics

Abstract: Objectives: It is generally accepted that maternal factors are important in maintaining the adequate nutritional status of young children. This study was aimed at verifying whether mother's socio-demographic (age and relationship status) and socio-economic features (education and professional status) differentiate the child's nutritional status. Material and Methods: A cross-sectional study was conducted between April and October 2013. Five hundred thirty mothers of preschool children from 5 different regions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
(62 reference statements)
1
3
0
Order By: Relevance
“…Results indicate that children of respondents that were informally employed were less likely to meet MMF guidelines. These findings are consistent with other studies, which also showed association between maternal employment and suboptimal child nutrition [2,18,21].…”
Section: Discussionsupporting
confidence: 93%
“…Results indicate that children of respondents that were informally employed were less likely to meet MMF guidelines. These findings are consistent with other studies, which also showed association between maternal employment and suboptimal child nutrition [2,18,21].…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, marital status significantly increased the likelihood of normal nutrition status of children 28 to 36-fold for mothers who were cohabiting, married, single or widowed compared with mothers who are separated or annulled, similar to Abuya et al’s (2012) findings among Kenyan children from two urban informal settlements whose mothers were “currently in union”. Among Polish children, a significant relationship was observed among those with single mothers in terms of percentage EAR for energy compared with children whose mothers were still living with spouses/partners (Potocka and Jacukowicz, 2017). “Acceptable” levels of household food consumption score and household perception of food security protected against malnutrition among the youngest age group four-fold and two-fold, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, toddlers from caregivers who were married or living with their partner had better diet quality. Studies show that diet quality differs among single versus married mothers, marked by lower intakes of fruits and vegetables and higher intake of energydense foods (47,48).…”
Section: Discussionmentioning
confidence: 99%